Zirconia-induced nanotwinned silicon nitride ceramic and method of making the same

CN122878145APending Publication Date: 2026-10-09CHINA ELECTRIC POWER RESEARCH INSTITUTE CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610978124.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-02
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0005]本发明的目的是解决对现有氮化硅陶瓷增韧后韧性不足的问题

Benefits of technology

本发明提供一种氧化锆诱导纳米孪晶增强氮化硅陶瓷,按质量百分数计,所述陶瓷的原料粉体包括:α型氮化硅:88%-93%;氧化钇稳定氧化锆:5%-10%;氧化镁:1%-2%。本发明的陶瓷通过氧化钇稳定氧化锆颗粒的应力诱导效应,使得陶瓷氮化硅晶粒内部可控生成高密度纳米孪晶,纳米孪晶界可有效偏转裂纹、阻碍位错运动,相变产生氧化锆四方相的压应力进一步抵消裂纹尖端应力,氮化硅纳米孪晶界强韧化与融合氧化锆四方-单斜相变增韧协同作用,实现材料韧性与强度同步提升,大幅提升氮化硅陶瓷的断裂韧性与抗弯强度。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122878145A_ABST
    Figure CN122878145A_ABST
Patent Text Reader

Abstract

The application provides a zirconia-induced nanotwin-reinforced silicon nitride ceramic and a preparation method thereof. The raw material powder of the ceramic comprises, in percentage by mass, 88-93% of alpha silicon nitride, 5-10% of yttrium oxide stabilized zirconia, and 1-2% of magnesium oxide. The ceramic of the application can generate high-density nanotwins in the interior of the ceramic silicon nitride grains through the stress-induced effect of the yttrium oxide stabilized zirconia particles. The nanotwin boundaries can effectively deflect cracks and hinder dislocation movement. The compressive stress generated by the tetragonal phase of zirconia through phase transition further offsets the stress at the crack tip. The strengthening and toughening of the silicon nitride nanotwin boundaries and the synergistic effect of the toughening of the fused zirconia tetragonal-monoclinic phase transition realize the synchronous improvement of the toughness and strength of the material, and greatly improve the fracture toughness and bending strength of the silicon nitride ceramic.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of advanced structural ceramics technology, specifically relating to a zirconia-induced nanotwin-reinforced silicon nitride ceramic and its preparation method. Background Technology

[0002] Silicon nitride ceramics possess high strength, high hardness, excellent high-temperature stability, thermal shock resistance, and corrosion resistance, making them a core material in the field of high-temperature structural ceramics and widely used in industries such as machinery, aerospace, electronics, and metallurgy. However, traditional silicon nitride ceramics generally have relatively low fracture toughness (6-8 MPa·m). 1 / 2 Its poor crack propagation resistance makes it prone to brittle fracture under impact loads and complex working conditions, which limits the expansion of its high-end application scenarios.

[0003] Currently, the strengthening and toughening methods for silicon nitride ceramics mainly focus on rare earth sintering aids optimization, grain boundary phase control, particle reinforcement, and fiber / whisker reinforcement. However, these methods face the following technical bottlenecks: First, conventional rare earth aids (Y₂O₃, La₂O₃, etc.) are costly, and the glassy phase at grain boundaries softens easily at high temperatures, reducing high-temperature mechanical properties. Second, traditional reinforcement methods can only achieve toughening through a single mechanism, resulting in limited improvement in toughness, and the fracture toughness is difficult to surpass the technical bottleneck of 10 MPa·m. 1 / 2 Therefore, existing silicon nitride ceramics, after toughening, lack sufficient toughness and the effect is unsatisfactory.

[0004] Accordingly, there is a need in the field for a new silicon nitride ceramic and its preparation method to solve the above problems. Summary of the Invention

[0005] The purpose of this invention is to solve the problem of insufficient toughness after toughening existing silicon nitride ceramics.

[0006] The objective of this invention is achieved through the following technical solution: This invention provides a zirconia-induced nanotwin-reinforced silicon nitride ceramic, wherein the raw material powder of the ceramic comprises, by mass percentage: α-type silicon nitride: 88%-93%; yttrium-stabilized zirconia: 5%-10%; and magnesium oxide: 1%-2%.

[0007] Preferably, the molar percentage of yttrium oxide in the yttrium-stabilized zirconium oxide is 2.5%-2.9%.

[0008] Preferably, the median particle size D50 of the α-type silicon nitride powder is ≤0.5μm, and the particle size of the yttrium oxide stabilized zirconium oxide powder is 50nm-100nm.

[0009] Preferably, the ceramic grains contain nanotwins and uniformly distributed tetragonal zirconium oxide phases, with the nanotwins having a size of 5nm-20nm.

[0010] Preferably, the fracture toughness of the ceramic is 10 MPa·m. 1 / 2 -12MPa·m 1 / 2 Flexural strength ≥1000MPa, relative density ≥98.5%.

[0011] Based on the same inventive concept, the present invention also provides a method for preparing the zirconium oxide-induced nanotwinned reinforced silicon nitride ceramic, comprising the following steps: Ingredient mixing: Weigh α-type silicon nitride, yttrium oxide-stabilized zirconium oxide, and magnesium oxide according to the raw material powder ratio of the ceramic, and perform wet ball milling to obtain a composite slurry with D50≤0.3μm; Drying and molding: The composite slurry is vacuum dried and sieved, and then isostatically pressed to obtain a green body with a theoretical density of 55%-60%. Hot pressing sintering: The green body is placed in a nitrogen atmosphere and hot pressing sintering is performed to obtain a dense nitrided ceramic green body; Quenching and aging: Immediately after sintering, the ceramic green body is placed in liquid nitrogen for liquid nitrogen quenching to induce the formation of nanotwins inside the silicon nitride grains; the quenched ceramic green body is subjected to low-temperature aging treatment to stabilize the nanotwin structure, thereby obtaining the zirconium oxide-induced nanotwin reinforced silicon nitride ceramic.

[0012] Preferably, in the ingredient mixing step, the wet ball milling uses a high-energy planetary ball mill with anhydrous ethanol and silicon nitride balls as the grinding media, the ball-to-material ratio is (7-9):1, the ball milling speed is 350 r / min-400 r / min, and the ball milling time is 12 h-16 h.

[0013] Preferably, in the drying and molding step, the composite slurry is placed in a vacuum drying oven at a drying temperature of 80℃-100℃ for 6h-8h.

[0014] Preferably, in the drying and molding steps, after drying, the silicon nitride balls are removed, and the mixture is passed through a 180-220 mesh sieve to obtain a mixed powder, which is then molded using a cold isostatic press at a pressure of 200-220 MPa and a holding time of 15-20 min.

[0015] Preferably, in the hot pressing sintering step: the green blank is placed in a graphite mold, the heating rate is 10℃ / min-15℃ / min, the sintering temperature is 1700℃-1800℃, the hot pressing pressure is 30MPa-35MPa, the hot pressing time is 1h-2h, and the nitrogen pressure in the nitrogen atmosphere is 0.1MPa-0.15MPa.

[0016] Preferably, in the quenching and aging steps, the quenching time of liquid nitrogen quenching is 5 min to 10 min.

[0017] Preferably, in the quenching and aging steps, the low-temperature aging treatment is performed using a box-type resistance furnace, with an aging temperature of 200℃-300℃ and a holding time of 12h-24h.

[0018] Compared with the prior art, the beneficial effects of the present invention are as follows: This invention provides a zirconia-induced nanotwin reinforced silicon nitride ceramic. The raw material powder of the ceramic, by mass percentage, comprises: α-type silicon nitride: 88%-93%; yttrium-stabilized zirconia: 5%-10%; and magnesium oxide: 1%-2%. Through the stress-induced effect of yttrium-stabilized zirconia particles, the ceramic of this invention allows for the controllable generation of high-density nanotwins within the silicon nitride grains. The nanotwin boundaries effectively deflect cracks and hinder dislocation movement. The compressive stress from the tetragonal zirconia phase generated by the phase transformation further offsets the stress at the crack tip. The synergistic effect of the strengthening and toughening of the silicon nitride nanotwin boundaries and the toughening effect of the fused tetragonal-monoclinic phase transformation of zirconia achieves a simultaneous improvement in both the toughness and strength of the material, significantly enhancing the fracture toughness and flexural strength of the silicon nitride ceramic. Attached Figure Description

[0019] Figure 1 This is an electron microscope magnified image of the zirconia-induced nanotwin-reinforced silicon nitride ceramic material of Example 1 of the present invention. Detailed Implementation

[0020] The following embodiments are provided to better understand the present invention and are not limited to the preferred embodiments described. They do not constitute a limitation on the content and scope of protection of the present invention. Any product that is the same as or similar to the present invention, derived by any person under the guidance of the present invention or by combining the features of the present invention with other prior art, falls within the protection scope of the present invention.

[0021] For any experimental steps or conditions not specified in this invention, the conventional experimental steps or conditions described in the literature in this field can be followed.

[0022] Research has revealed that existing literature only mentions the coherent interface (quasi-twin structure) of silicon nitride α / β phases or a small number of defective twins during annealing, failing to achieve controllable induction and large-scale preparation of twins, and lacking a mature scheme for synergistic toughening mechanisms. Yttrium-stabilized zirconia (3YSZ) possesses a typical phase transformation toughening effect. Tetragonal zirconia undergoes a martensitic phase transformation under stress, generating compressive stress within the ceramic matrix, effectively hindering crack propagation. Simultaneously, during silicon nitride sintering and subsequent heat treatment, zirconia particles can overcome the technical barrier of twin formation due to high fault energy in silicon nitride through lattice matching and stress field induction, achieving controllable generation of nanotwins within the grains. Based on this, the silicon nitride ceramic of this invention, toughened by combining the dual mechanisms of zirconia phase transformation toughening and silicon nitride nanotwin strengthening, exhibits high ceramic toughness, is free of rare earth doping, and is low in cost.

[0023] Specifically, the present invention provides a zirconia-induced nanotwinned reinforced silicon nitride ceramic, wherein the raw material powder of the ceramic comprises, by mass percentage: α-type silicon nitride (α-Si3N4): 88%-93%; yttrium-stabilized zirconia: 5%-10%; magnesium oxide (MgO): 1%-2%.

[0024] Among them, magnesium oxide is used as a sintering aid, the molar percentage of yttrium oxide in yttrium-stabilized zirconium oxide is 2.5%-3%, the purity of α-type silicon nitride powder is ≥99.5%, the median particle size D50 of α-type silicon nitride powder is ≤0.5μm, and the particle size of yttrium-stabilized zirconium oxide powder is 50nm-100nm, in order to avoid stress concentration caused by large particles.

[0025] The ceramic grains in this invention contain nanotwins (5nm-20nm in size) and uniformly distributed tetragonal zirconia phase. By combining the toughening mechanisms of zirconia tetragonal-monoclinic phase transformation and silicon nitride nanotwin boundary strengthening, simultaneous improvement in toughness and strength is achieved. Specifically, the grain boundaries of the nanotwins effectively deflect cracks and hinder dislocation movement, while the compressive stress generated by the zirconia phase transformation further offsets the stress at the crack tip.

[0026] It should be noted that when the twin size exceeds 20 nm, the twin boundary spacing increases, and dislocations tend to accumulate in large quantities within the twins, forming local stress concentrations and inducing microcracks. When the twin size is less than 20 nm, the twin boundary spacing is comparable to the mean free path of dislocations, which can effectively block dislocation slip and force dislocations to accumulate or cross-slip at the twin boundaries, thereby significantly improving the yield strength and deformation resistance of the material.

[0027] The 5nm to 20nm small-sized nanotwins of the present invention are uniformly distributed, which avoids local stress concentration and maintains the integrity of the matrix.

[0028] Ultimately, the fracture toughness of the silicon nitride ceramic of this invention is 10 MPa·m.1 / 2 -12MPa·m 1 / 2 Flexural strength ≥1000MPa, relative density ≥98.5%.

[0029] Based on the same inventive concept, the present invention also provides a method for preparing the above-mentioned zirconium oxide-induced nanotwinned reinforced silicon nitride ceramic, comprising the following steps: S1. Mixing of raw materials: Weigh α-type silicon nitride (α-Si3N4), yttrium-stabilized zirconium oxide (3YSZ), and magnesium oxide (MgO) according to the above-mentioned raw material powder ratio for ceramics, and perform wet ball milling to obtain a uniformly mixed composite slurry with D50≤0.3μm, which provides higher sintering activity and makes it easier to sinter densely.

[0030] Specifically, the wet ball milling uses a high-energy planetary ball mill with anhydrous ethanol and silicon nitride balls as the grinding media, the ball-to-material ratio is (7-9):1, the ball milling speed is 350 r / min-400 r / min, and the ball milling time is 12 h-16 h.

[0031] S2. Drying and molding: The composite slurry is vacuum dried, sieved and then isostatically pressed to obtain a green body with a theoretical density of 55%-60%. Specifically, the composite slurry is placed in a vacuum drying oven and dried at a temperature of 80℃-100℃ for 6-8 hours. After drying, the silicon nitride balls are removed, and the mixture is passed through a 180-220 mesh sieve to obtain a mixed powder. This powder is then formed using a cold isostatic press at a pressure of 200MPa-220MPa and a holding time of 15-20 minutes.

[0032] S3. Hot pressing sintering: The green body is placed in a nitrogen atmosphere and hot pressing sintered to obtain a dense nitrided ceramic body. Specifically, the green blank is placed in a graphite mold and then placed in a hot-pressing sintering furnace. The heating rate is 10℃ / min-15℃ / min, the sintering temperature is 1700℃-1800℃, the hot-pressing pressure is 30MPa-35MPa, the holding time is 1h-2h, and the nitrogen atmosphere pressure is 0.1MPa-0.15MPa. The nitrogen atmosphere is used to prevent the decomposition of silicon nitride.

[0033] S4. Quenching and Aging: Immediately after sintering, the ceramic green body is placed in liquid nitrogen for liquid nitrogen quenching to induce the formation of nanotwins inside the silicon nitride grains. That is, the internal stress field generated by rapid cooling, combined with the lattice induction effect of zirconia particles, generates nanotwins inside the silicon nitride grains. The quenched ceramic green body is then subjected to low-temperature aging treatment to stabilize the nanotwin structure and promote the uniform distribution of the tetragonal phase of zirconia, resulting in zirconia-induced nanotwin reinforced silicon nitride ceramic.

[0034] This invention addresses the gap in existing technologies regarding the lack of controllable preparation methods and systematic performance data for silicon nitride nanotwins. By inducing stress field and lattice matching of 3YSZ zirconia particles, combined with liquid nitrogen quenching, high-density uniform nanotwins with sizes ranging from 5nm to 20nm are controllably generated within silicon nitride grains. This achieves a synergistic effect of twinning toughening and phase transformation toughening, significantly improving the fracture toughness and flexural strength of silicon nitride ceramics. Furthermore, this invention abandons traditional high-cost rare-earth sintering aids, using MgO as a single aid, reducing raw material costs by more than 20%. Simultaneously, it avoids the high-temperature softening problem of rare-earth glass phases at grain boundaries, thus improving high-temperature mechanical properties.

[0035] The following specific embodiments were obtained by selecting different raw material composition ratios and preparation process parameters for the above-mentioned zirconia-induced nanotwin reinforced silicon nitride ceramics.

[0036] Examples 1-5 Table 1 shows a comparison of the raw material composition ratios and preparation process parameters in the zirconia-induced nanotwinned silicon nitride ceramics of Examples 1-5, as follows: Table 1

[0037] It should be noted that Table 1 above mainly lists the key preparation parameters. For preparation parameters not listed, those skilled in the art can use the defined parameter range or conventional values.

[0038] Results Test The results of testing the zirconia-induced nanotwinned reinforced silicon nitride ceramic samples of Examples 1-5 are shown in Table 2: Table 2

[0039] Table 2 is a comparison table of performance parameters for Examples 1-5.

[0040] like Figure 1 As shown, in Example 1, the nanotwins and zirconium oxide tetragonal phase are evenly distributed in the ceramic grains, providing a basis for the synergistic effect of toughness and strength.

[0041] A comparison of Tables 1 and 2 shows that the fracture toughness of the silicon nitride ceramics in Examples 1-5 is within the range of 10 MPa·m. 1 / 2 -12MPa·m 1 / 2 The flexural strength is ≥1000MPa, the relative density is ≥98.5%, and the nanotwin size ranges from 5nm to 20nm. Among them, Example 1 has the best balanced performance indicators, with a fracture toughness ranging from 11.2MPa·m. 1 / 2 It has a flexural strength of 1080 MPa, a relative density of 99.1%, and an average nanotwin size of 8 nm.

[0042] The above are merely embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention are included within the scope of the claims of the present invention pending approval.

Claims

1. A zirconia-induced nanotwinned reinforced silicon nitride ceramic, characterized in that, The raw material powder of the ceramic, by mass percentage, comprises: α-type silicon nitride: 88%-93%; yttrium oxide stabilized zirconium oxide: 5%-10%; magnesium oxide: 1%-2%.

2. The zirconia-induced nanotwinned reinforced silicon nitride ceramic according to claim 1, characterized in that, The molar percentage of yttrium oxide in the yttrium oxide-stabilized zirconium oxide is 2.5%-2.9%.

3. The zirconia-induced nanotwinned reinforced silicon nitride ceramic according to claim 1, characterized in that, The median particle size D50 of the α-type silicon nitride powder is ≤0.5μm, and the particle size of the yttrium oxide stabilized zirconium oxide powder is 50nm-100nm.

4. The zirconia-induced nanotwinned reinforced silicon nitride ceramic according to claim 1, characterized in that, The ceramic grains contain nanotwins and uniformly distributed tetragonal zirconium oxide phases, with the nanotwins having a size of 5nm-20nm.

5. The zirconia-induced nanotwinned reinforced silicon nitride ceramic according to claim 1, characterized in that, The fracture toughness of the ceramic is 10 MPa·m. 1 / 2 -12MPa·m 1 / 2 Flexural strength ≥1000MPa, relative density ≥98.5%.

6. A method for preparing zirconia-induced nanotwinned reinforced silicon nitride ceramic according to any one of claims 1-5, characterized in that, Includes the following steps: Ingredient mixing: Weigh α-type silicon nitride, yttrium oxide-stabilized zirconium oxide, and magnesium oxide according to the raw material powder ratio of the ceramic, and perform wet ball milling to obtain a composite slurry with D50≤0.3μm; Drying and molding: The composite slurry is vacuum dried and sieved, and then isostatically pressed to obtain a green body with a theoretical density of 55%-60%. Hot pressing sintering: The green body is placed in a nitrogen atmosphere and hot pressing sintering is performed to obtain a dense nitrided ceramic green body; Quenching and aging: Immediately after sintering, the ceramic green body is placed in liquid nitrogen for liquid nitrogen quenching to induce the formation of nanotwins inside the silicon nitride grains; the quenched ceramic green body is subjected to low-temperature aging treatment to stabilize the nanotwin structure, thereby obtaining the zirconium oxide-induced nanotwin reinforced silicon nitride ceramic.

7. The method for preparing zirconia-induced nanotwinned reinforced silicon nitride ceramics according to claim 6, characterized in that, In the ingredient mixing step, the wet ball milling uses a high-energy planetary ball mill with anhydrous ethanol and silicon nitride balls as the grinding media, the ball-to-material ratio is (7-9):1, the ball milling speed is 350r / min-400r / min, and the ball milling time is 12h-16h.

8. The method for preparing zirconia-induced nanotwinned reinforced silicon nitride ceramics according to claim 6, characterized in that, In the drying and molding step, the composite slurry is placed in a vacuum drying oven at a drying temperature of 80℃-100℃ for 6-8 hours.

9. The method for preparing zirconia-induced nanotwinned reinforced silicon nitride ceramics according to claim 6, characterized in that, In the drying and molding steps, after drying, the silicon nitride balls are removed, and the mixture is passed through a 180-220 mesh sieve to obtain a mixed powder. The powder is then molded using a cold isostatic press with a molding pressure of 200-220 MPa and a holding time of 15-20 minutes.

10. The method for preparing zirconia-induced nanotwinned reinforced silicon nitride ceramics according to claim 6, characterized in that, In the hot pressing sintering step: the green blank is placed in a graphite mold, the heating rate is 10℃ / min-15℃ / min, the sintering temperature is 1700℃-1800℃, the hot pressing pressure is 30MPa-35MPa, the hot pressing time is 1h-2h, and the pressure of the nitrogen atmosphere is 0.1MPa-0.15MPa.

11. The method for preparing zirconia-induced nanotwinned reinforced silicon nitride ceramics according to claim 6, characterized in that, In the quenching and aging steps, the quenching time for liquid nitrogen quenching is 5 min to 10 min.

12. The method for preparing zirconia-induced nanotwinned reinforced silicon nitride ceramic according to claim 6, characterized in that, In the quenching and aging steps, the low-temperature aging treatment is carried out in a box-type resistance furnace, with an aging temperature of 200℃-300℃ and a holding time of 12h-24h.